Membumikan Al-Qur'an Dalam Tradisi Khatmil Qur'an di Ponpes Wali Songo Situbondo - Rohmah, Umi Nuriyatur (LPPM Sekolah Tinggi Ilmu Al-Qur'an Wali Songo Situbondo, 2022)
The study examines the tradition of the khatmil Qur’an in P.P. Walisongo Situbondo. The focus of this study is to know the practice and meaning of khatmil Qur’an implemented on the night of Tuesday legi in P.P. Walisongo Situbondo. This research is descriptive, that is, to explain systematically the living Qur’an practices that occur in P.P. Walisongo Situbondo. This study used phenomenology approach with Karl Manneim's knowledge sociology theory. This study concluded that, first, the khatmil Qur’an activity implemented on the night of Tuesday legi in P.P. Walisongo Situbondo is not only followed by santri, but also followed by the surrounding societies. The reading of the verses of the Qur’an is done in the manner of bil hifdzi that is, reading the Qur’an without seeing mushaf. Secondly, in the imposition of khatmil Qur’an activitiy in P.P Walisongo, based on Karl Mannheim’s theory, was found three catagories of meaning, (1) objective meaning as a series of activities that perfomed by santri and society, from reading al- to prayer together; (2) expressive meaning as a motivation to understand the Qur’an, additional insights of knowledge, gaining blessing from the reading of the Qur’an and means to facilitate santri’s recitation; (3) the documentary meaning as a container in spreading and grounding the Qur’an.